Genome of Ca. Pandoraea novymonadis, an Endosymbiotic Bacterium of the Trypanosomatid Novymonas esmeraldas - Kostygov, Alexei Y.; Butenko, Anzhelika; Nenarokova, Anna; Tashyreva, Daria; Flegontov, Pavel; Lukeš, Julius; Yurchenko, Vyacheslav (Frontiers in Microbiology, 2017)
We have sequenced, annotated and analyzed the genome of Ca. Pandoraea novymonadis, a recently described bacterial endosymbiont of the trypanosomatid Novymonas esmeraldas. When compared with genomes of its free-living relatives, it has all the hallmarks of the endosymbionts' genomes, such as significantly reduced size, extensive gene loss, low GC content, numerous gene rearrangements, and low codon usage bias. In addition, Ca. Pandoraea novymonadis lacks mobile elements, has a strikingly low number of pseudogenes and almost all genes are single copied. This suggests that it already passed the intensive period of host adaptation, which still can be observed in the genome of Polynucleobacter necessarius, a certainly recent endosymbiont. Phylogenetically, Ca. Pandoraea novymonadis is more related to Polynucleobacter necessarius, an intracytoplasmic bacterium of free-living ciliates, than to Ca. Kinetoplastibacterium spp., the only other known endosymbionts of trypanosomatid flagellates. As judged by the extent of the overall genome reduction and the loss of particular metabolic abilities correlating with the increasing dependence of the symbiont on its host, Ca. Pandoraea novymonadis occupies an intermediate position Polynucleobacter necessarius and Ca. Kinetoplastibacterium spp. We conclude that the relationships between Ca. Pandoraea novymonadis and Novymonas esmeraldas are well-established, although not as fine-tuned as in the case of Strigomonadinae and their endosymbionts.